Systematic Literature Review (SLR): Gen Z Entrepreneurial Performance Based on Internal Factors - Puan Nabilla; Asmar Yulastri; Yuliana Yuliana (Universitas Sebelas Maret, 2025)
Indonesia as a developing country continues to encourage its economic growth through various sectors, one of which is entrepreneurship which is now largely driven by Generation Z. This generation has great potential in creating new businesses due to its proximity to technology, but still faces various internal obstacles such as low managerial skills, financial literacy, and readiness to face business risks. This research was conducted using a Systematic Literature Review (SLR) approach. The purpose of this study is to identify and synthesize internal factors that influence the entrepreneurial performance of Gen Z comprehensively as an effort to support entrepreneurship development. Research data was obtained from Scopus for the period 2015-2025. In addition, restrictions were also made with the keyword’s